Pampa Corte Plus: uma ferramenta de simulação para o ensino, pesquisa e extensão na região do Pampa - Brasil, Miguel Augusto Bauermann (2023)
Livestock activity has a long tradition in the Pampa Biome and is recognized for contributing to biodiversity conservation. However, it is often associated with inadequate or poorly planned systems, which results in the replacement of grazing areas by crops. This secondary role attributed to livestock in the Gaúcha campaign largely stems from the simple lack of information among producers and technicians, and a lack of understanding about the sustainable use of this biome. In this context, universities have the responsibility of training technicians and producers, but face challenges in including university extension in the curriculum. This thesis presents the Pampa Corte Plus approach, an innovative strategy for improving livestock in the Pampa Biome, as it allows for the simulation of different strategies and their effects on animal weight gain, while also being a valuable tool for decision-making and advancing academic knowledge in the field. To validate the approach, a multi-platform web application called Pampa Corte Plus was created. The tool includes two simulation modules, an academic and a livestock one, and is an example of how the use of information and communication technologies can strengthen the ties between teaching, research, and university extension. The tool's interface is intuitive and easy to navigate, making it accessible even for those with little previous experience in the field. The tool was developed to be compatible with various devices and operating systems, ensuring that users can access it from anywhere with internet access and at any time, with the same quality and performance. The results obtained in a controlled environment were very promising, and in the real-world application, there was a good reception from respondents, indicating the relevance and usefulness of the approach for livestock.